Preparation for Meaningful Work and Life: Urban High School Youth’s Reflections on Work-Based Learning 1 Year Post-Graduation - Kenny, Maureen E.; Catraio, Christine; Bempechat, Janine; Minor, Kelly; Olle, Chad; Blustein, David L.; Seltzer, Joanne (Frontiers in Psychology, 2016)
The challenges confronted by low-income high school students throughout school and across the transition to higher education and employment are well-documented in the US and many other nations. Adopting a positive youth development perspective (Lerner et al., 2005), this study reports findings from interviews with 18 low-income, racially and ethnically diverse graduates of an urban Catholic high school in the US. The interviews were designed to shed light on the post-high school experiences of urban high school graduates and to understand how students construct meaning about the value of school and work-based learning (WBL) in their preparation for meaningful work and life. The interviews highlight the perceived value of the academic and non-cognitive preparation students experienced through high school and WBL in relation to the challenges they encountered along the pathway to post-high school success and decent work. Overall, the findings suggest the potential of WBL for low-income youth in facilitating access to resources that build academic and psychological/non-cognitive assets, while also illustrating the role of structural and contextual factors in shaping post-high school transitions and access to meaningful work and life opportunities.